Diseño e implementación de un sistema de medición, análisis y control de señales biomédicas - Córdova Hernández, Erika Zuleima (2018)
This thesis presents a control, measurement and monitoring system for biomedical signals in elderly patients and in people with temporary disability, which due to their health condition require a great care and quantity of medicines, said consumption if the indications are not respected, can cause conditions or contradictions in the body. Patient monitoring is done through the use of modules for the control of biomedical signals such as: blood pressure, heart rate and body temperature. The results obtained will be displayed on a graphic screen, in turn the results can be observed in a database, in case there is any complication in any of these biomedical signals the system sends warning messages to the trusted doctor or the person in charge of the patient, through the GSM network. This project has a posology system for the patient according to the indications defined by the treating physician, which is responsible for controlling the time of intake of medicines, its basic structure and easy to use provides comfort and instant support for the patient consumption of it. This system has an easy to handle structure, due to its design and graphical interface that makes its interaction with the measurement modules carried out without complications and with success.